1998
DOI: 10.1046/j.1471-4159.1998.70010066.x
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Induces Necrosis and Apoptosis in Hippocampal Neurons

Abstract: A diverse body of evidence indicates a role for the lipid biomediator lysophosphatidic acid (LPA) in the CNS. This study identifies and characterizes the induction of neuronal death by LPA. Treatment of cultured hippocampal neurons from embryonic rat brains with 50~eM LPA resulted in neuronal necrosis, as determined morphologically and by the release of lactate dehydrogenase. A concentration of LPA as low as 10~iMled to the release of lactate dehydrogenase. In contrast, treatment of neurons with 0.1 or 1.0 j.t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 73 publications
4
60
0
Order By: Relevance
“…We found that LPA promoted apoptosis of early human NS/PCs, as revealed by neurosphere formation assay, which is consistent with some NS/PC and neuroblast studies performed in rodents ( 16,17,38,57,58 ) but differs with others in which LPA improves cell survival ( 16,38 ) or proliferation ( 13,35,59 ). In human cells, we previously showed that LPA does not modify apoptosis of older hESCderived NS/PCs ( 39 ) as, when two-week-old hESC-derived within minutes; Fig.…”
Section: Lpa Induces Rhoa Activationsupporting
confidence: 90%
“…We found that LPA promoted apoptosis of early human NS/PCs, as revealed by neurosphere formation assay, which is consistent with some NS/PC and neuroblast studies performed in rodents ( 16,17,38,57,58 ) but differs with others in which LPA improves cell survival ( 16,38 ) or proliferation ( 13,35,59 ). In human cells, we previously showed that LPA does not modify apoptosis of older hESCderived NS/PCs ( 39 ) as, when two-week-old hESC-derived within minutes; Fig.…”
Section: Lpa Induces Rhoa Activationsupporting
confidence: 90%
“…During such events, which damage the blood-brain barrier, levels of LPA within the nervous system are hypothesized to increase to 10 M (reviewed in [33,34]). LPA has been shown to stimulate astrocytic proliferation [7,34], and depending on its concentration, it has also been described as promoting death of hippocampal neurons, by apoptosis (1 M) or by necrosis (10 M) [35]. Moreover, LPA has recently been described as cytotoxic to the neuromicrovascular endothelium [36].…”
Section: Resultsmentioning
confidence: 99%
“…LPA injections into mouse brain induce astrocyte reactivity at the site of the injury [115] , while in the spinal cord following trauma, LPA induces neuropathic pain and demyelination [116][117][118][119][120][121] . LPA can stimulate astrocytic proliferation [87,111] and, depending on its concentration, it can promote death of hippocampal neurons by apoptosis (1 M ) or by necrosis (10 M ) [122] . Moreover, LPA mediates microglial activation [81] and is cytotoxic to the neuromicrovascular endothelium [123] .…”
Section: Lpa/s1p Signalling In the Injured Cns Through Neural Stem/prmentioning
confidence: 99%